THEORETICAL AND METHODOLOGICAL ASPECTS OF USING INFORMATION ANDCOGNITIVE TECHNOLOGIES IN THE TRAINING OF TRANSPORT SPECIALISTS - Lavrentieva Olena; Krupskyi Oleksandr (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article addresses how to improve the professional training of specialists in the transport industry using information and cognitive technologies. The article aims to study and explain the problems, opportunities, and prospects of implementing and using information and cognitive technologies in the educational environment, as well as the specifics of their implementation for teaching and learning in educational and professional programs for the transport specialists’ training. The following methods of semantic and comparative analysis, classification, generalization, and systematization, as well as competency-based, technological, and creative development approaches were used in the research. It has been found that cognitive technologies in the context of teaching and learning involve the use of methods and tools, which are based on understanding and activating cognitive processes such as thinking, memory, and attention. In cognitive learning, the educational process focuses not on absorbing information but on understanding the internal connections of the studied subjects, which encourages students to engage in dialogical, exploratory thinking, and increases mental activity concentration. By complementing information technologies with cognitive ones, which take into account the individual and general cognitive students’ abilities, it is possible not only to encourage professional training but also to enhance the overall cognitive efficiency of future specialists. For educators, these technologies facilitate the use of ICT as cognitive tools for transitioning from traditional teacher-centred methods to constructivist student-centred approaches. It has been established that information-cognitive technologies combine methods and algorithms based on insights into the cognition processes, learning, communication, and information processing, grounded in the achievements of neuroscience, digital and information technologies, and the mathematical modelling of consciousness. In the educational process, they are designed to support students in setting and solving creative tasks that are difficult to formalize, as well as to reveal and effectively operate their cognitive potential. In the professional training of students, certain information-cognitive technologies can be applied both with and without the use of computer systems. These include technologies for developing critical thinking, creatively developmental technologies, project technologies, foresight methodologies, problem-based learning technologies, mastery learning technologies, mental activity activation technologies, case studies, gaming technologies, visualization and data representation technologies, and learning through practice. Additionally, the use of multimedia technologies, scribing, virtual and augmented reality, project technologies based on networking, gamification, interactive technologies, primarily group work technologies, open, distance, and blended learning technologies, and also the Internet of Things, Blockchain, Big Data, expert systems, SMART technologies, and artificial intelligence significantly enhances the quality of training students in proficiency transport area. It has been concluded that information and cognitive technologies provide interactive, personalized, and practically oriented learning, contribute to the development of student’s critical thinking, and for future transport specialists can optimize logistics processes, automate diagnostics, repair, and operation of vehicles, in addition, increase the specialist’s adaptability to the complex conditions of the modern and future professional environment.